Explaining electricity forward premiums: Evidence for the weather uncertainty effect - Frank Obermüller (Institute of Energy Economics at the University of Cologne (EWI), 2017)
With the increasing share of volatile renewable energies, weather prediction becomes more important to electricity markets. The weather-driven uncertainty of renewable forecast errors could have price increasing impacts. This research sets up an analytic model to show that the day-ahead optimal bidding under uncertain renewable production is below the expected production and thus price increasing. In a second step, the price increasing effect on forward premiums by specific weather types and their renewable production uncertainty is proved via empirical methods. Weather types are identified in which renewable production is harder to predict. The findings connect weather dependent renewable forecast uncertainty to forward premiums and support the consideration of weather types in price forecasting models.
Keywords: D21; D22; D41; D81; P18; Q41; Q42; Q47; 330; Forward premium; Weather type; Uncertainty; Volatile renewable production